Is globalisation linked to CO2 emission? Evidence from OECD nations - Ivanovski, Kris; Hailemariam, Abebe (Springer Nature, 2021)
An extensive number of studies uses trade-to-GDP as a proxy for globalisation in environmental research. Globalisation encompasses much more than just trade in goods. Globalisation is the integration of various countries and includes spillovers of ideas and technology, financial flows, the worldwide movement of labour, and national governments meeting on an international level in a bid to solve social and political problems. This study considers the effect of globalisation on carbon dioxide emissions by using a more flexible and comprehensive measure based on the KOF globalisation index for a panel of 21 OECD nations covering the period 1970–2014. Since the globalisation process is not uniform across countries and time, we use a fully-fledged nonparametric technique to estimate the time-varying coefficient and trend functions. Our results show that the effect of globalization on CO2 emissions is positive up until 2000, then switches to turns negative thereafter.